Frequency of occurrence of knock-kneed and bow-legged knees for children and young people in school age - Siminska, Joanna; Bukowska, Weronika; Ratuszek–Sadowska, Dorota; Nowacka, Krystyna; Hagner, Wojciech (Journal of Education, Health and Sport, 2017)
Lower limb faults are one of the most common defects in school-age children and are now a problem in our society. Currently there is a trend towards low physical activity among children. Most young people prefer to spend time sitting down without taking physical activity or limiting it to the minimum. This results in lowering muscle tone, weight gain - manifesting as being overweight or obese. School children often complain of spinal pain as well as lower back pain. We have many disadvantages in the lower limb - but the most common are the knee and the knee. These defects require a comprehensive, individual physiotherapeutic procedure that will help correct the defect. Applied rehabilitation affects the strength of the muscle, contributes to correcting the defect of the lower limb as well as reduces the occurring pain.